Territorial justice and equity criteria – spatial planning in Ticino. - Cometta, Mosè (Copernicus Publications, 2021)
This paper analyses from a philosophical and interdisciplinary point of view two master plans of the canton Ticino – the first one from 1990, Keynesian, and the second one from 2009, neoliberal. The differences between the former and the latter are highlighted on a conceptual level. While the former stresses the importance of rebalancing and maintaining internal solidarity between the regions of the canton, the latter aims to make the canton more competitive and specialised. The discussion highlights how this type of analysis, by showing the political and moral concepts and criteria underlying a master plan, favours their political discussion and thus, ultimately, the implementation of a more inclusive planning process.
Keywords: Regionalentwicklungsplan; Raumplanung; Planungsansatz; Vergleich; Analyse; Interpretation; Regionale Disparität